Supplementation with Ginseng, Lilii Bulbus, and Poria induces alterations in the serum metabolic profile of healthy adults. Issue 18 (24th August 2022) - Xie, Fangzhi; Chen, Liang; Jin, Shuna; Qiu, Feng; Kan, Juntao; Li, Yujie; Wang, Hanjin; Huang, Min; Sun, Xiaojie; Du, Jun; Li, Yuanyuan
Abstract : The preventive and therapeutic effects of herbal supplementation containing Ginseng, Lilii Bulbus, and Poria (GLP) on inflammation and oxidative stress in healthy adults have been demonstrated. Abstract : The preventive and therapeutic effects of herbal supplementation containing Ginseng, Lilii Bulbus, and Poria (GLP) on inflammation and oxidative stress in healthy adults have been demonstrated in our previous studies. However, the underlying mechanisms of organism protection by GLP remain unclarified, and few studies have used metabolomics to investigate comprehensive changes before and after GLP supplementation. Based on previous research, we conducted a placebo-controlled trial among 82 healthy adults in Wuhan, China, using a metabolomics approach with ultra-performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS/MS) and multivariate statistical methods to analyze serum metabolite alterations in participants before and after GLP supplementation. Furthermore, 14 discriminant metabolites related to lipid metabolism, inflammation and oxidative stress, energy metabolism, and coenzyme A metabolism were significantly different between the before- and after-GLP groups ( P < 0.0001). Nine metabolites were significantly decreased in the serum samples from the after-GLP group compared with the before-GLP group, while five metabolites were significantly increased. These metabolites could be critical components associated with the anti-inflammatory, antioxidant, and hypolipidemic activities of GLP, indicating the potential complementary role of GLP supplements in the primary prevention of dysfunctional metabolism caused by potential diseases such as cardiovascular disease. This study provides a valuable reference for cardiovascular health protection and disease prevention.